Analysis of the Benefits and Costs of CalMHSA's Investment in Applied Suicide Intervention Skills Training (ASIST) - Ashwood, J. Scott (RAND Corporation, 2015)
Estimates the possible reductions in suicide attempts resulting from investment in ASIST and estimates the financial return to Californians from reduced medical costs associated with suicide attempts and increased earnings from each life saved.